Systemic lupus erythematosus with hypothermia and Wallenberg’s syndrome as signs of brainstem encephalitis: A grand rounds case - Shiratani, Reo; Shibahara, Takayuki; Shiba, Mikio; Murao, Haruka; Park, Jeong Hoon; Tada, Tomomi; Ishikawa, Nachi; Fujimoto, Jun; Jinno, Junki; Tatsumi, Makoto; Yamada, Tomoki; Higuchi, Yoshiharu; et al. (Lupus, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease that causes inflammation and organ damage. However, brain-stem encephalitis is rare in patients with SLE. We report a rare case of a patient with incipient SLE who simultaneously presented with brainstem encephalitis and cardiomyopathy. An 18-year-old woman was admitted to our hospital with fever, polyarthralgia, and malar rash. Laboratory tests revealed leukopenia, thrombocytopenia, proteinuria, an elevated anti-double-stranded deoxyribonucleic acid antibody titer, and hypocomplementemia. She was diagnosed with SLE and treated with an intermediate dose of prednisolone. Her fever disappeared 2 days later, but high-grade fever reappeared, and a high dose of prednisolone was administered from the eighth day of hospitalization. On the tenth day of hospitalization, she developed a headache, hypothermia, dysphagia, respiratory failure, and myocarditis. Brain magnetic resonance imaging indicated brainstem encephalitis. Under ventilator management, the patient received intravenous methylprednisolone pulse therapy, cyclophosphamide, and plasma exchange. Her general condition improved, however, dysphagia and hoarseness persisted, and Wallenberg’s syndrome was diagnosed. Our findings suggest that patients with SLE can present with Wallenberg’s syndrome as a sign of brainstem encephalitis and that early aggressive immunotherapy can be effective in patients with brainstem encephalitis and cardiomyopathy associated with SLE.